TUNINGENIE - AN AUTOTNUNING FRAMEWORK FOR OPTIMIZATION OF PARALLEL APPLICATIONS - Ivanenko, П.А.; Doroshenko, А.Ю. (Journal of Information Technologies in Education (ITE), 2013)
There are proposed software tools for automatic generating autotuners – special kind of applications to optimize running parallel application software in target computing environment.